2016
DOI: 10.3892/ol.2016.4488
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 expression and its association with wighteone metabolite response in HER2-positive breast cancer cells

Abstract: Abstract.It is well known that heat shock protein 90 (HSP90) overexpression is correlated with poor prognosis and chemo-resistance in human malignant cancers. At the same time, wighteone, or 6-prenyl-5,7,4'-trihydroxyisoflavone, a major isoflavone component of the ornamental tall tree Erythrina suberosa, has been demonstrated to exhibit a potent anti-proliferative effect on human leukemia HL-60 cancer cell lines. In this study, the effects of wighteone on the proliferation of HER2-positive breast cancer cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…HSP90 is a molecular chaperone protein that is essential for the maintenance and progression of cancer . In addition, overexpression of HSP90 is reported in several malignancies and is correlated with a poor prognosis . Our results showed that HSP90 was overexpressed in angiosarcoma cell lines in vitro and in tissues derived from patients with angiosarcoma.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…HSP90 is a molecular chaperone protein that is essential for the maintenance and progression of cancer . In addition, overexpression of HSP90 is reported in several malignancies and is correlated with a poor prognosis . Our results showed that HSP90 was overexpressed in angiosarcoma cell lines in vitro and in tissues derived from patients with angiosarcoma.…”
Section: Discussionsupporting
confidence: 49%
“…10 In addition, overexpression of HSP90 is reported in several malignancies [33][34][35] and is correlated with a poor prognosis. 33,36 Our results showed that HSP90 was overexpressed in angiosarcoma cell lines in vitro and in tissues derived from patients with angiosarcoma.…”
Section: Discussionmentioning
confidence: 66%
“…They showed that both MLF and AIF demonstrated the most potent cytotoxicity with IC 50 of~20 µM in HL60 cells and could induce apoptosis through inhibition of NF-kB factor (through the signal transducer of activation (STAT) pathway) [3]. Moreover, wighteone, an isoflavone derived from E. suberosa stem bark as mentioned above, demonstrated anticancer effects in MCF-7 HER2-positive cells (human mammary cancer cells) mediated by the heat shock protein 90 (HSP90), again increasing apoptosis and reducing cell proliferation [29]. Is it notable that wighteone can be found in different plants: Cudrania tricuspidata (Carrière) Bureau, Ficus tikoua Bur., Maclura pomifera (Raf.)…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Xu et al (16) and Ahn et al (21) demonstrated that high HSP90 protein expression is related to the metastasis and invasion of CRC. Preclinical studies and early clinical trials have confirmed the efficacy of HSP90 inhibition as a target therapy for many solid tumors (6,16,19,20). Recent data showed the therapeutic utility of HSP90 inhibitors in patients resistant to tyrosine kinase inhibitors (7,18).…”
mentioning
confidence: 98%
“…Many HSP90 client proteins are involved in processes such as proliferation, apoptosis, and cycle progression (16,18). Several reports have analyzed HSP90 expression in solid tumors and found that HSP90 expression is correlated with clinical prognosis, (5,16,19,20). Xu et al (16) and Ahn et al (21) demonstrated that high HSP90 protein expression is related to the metastasis and invasion of CRC.…”
mentioning
confidence: 99%